Fourmoon Start-Up Management Development Start-Up Fourmoon (Multifunctional Painted Shawl) - Nisa, Apriliana Putri Khairun; Budiarta, I Dewa Putu Gede; Gulendra, I Wayan (PROGRAM STUDI SENI MURNI ISI DENPASAR, 2024)
The Multifunctional Painted Shawl is a special product from Fourmoon that prioritizes functionality and beauty. Based on Wikipedia, a shawl is traditional Indonesian clothing in the form of a long cloth and it is usually worn by women. This scarf is specially designed to have multiple functions in just one item. In addition, the multiple function of Fourmoon Shawl also has aesthetic value on its surface design and additional prada. The aims of this text are, 1). To Find out the Transfer of Entrepreneurial Knowledge to the Agung Bali Collection for the development of fourmoon start-up management (multifunctional Painted Shawls). 2). Finding out about the transfer of entrepreneurial skills to the Agung Bali Collection for the development of fourmoon start-up management (Painted multifunctional shawl). 3). Finding out about the transfer of Marketing Knowledge and Technology to the Agung Bali Collection. This type of research includes quantitative research and observation as a data collection method. The results of this MBKM are, 1). There are 9 functions of painted shawl products produced by fourmoon 2). The marketing that the writer does is offline and online way such as Instagram. The writer also applies a custom-order system 3). Developing insight such as prada adding with the canting massage technique.